2019
DOI: 10.1089/trgh.2019.0022
|View full text |Cite
|
Sign up to set email alerts
|

Transgender and Nontrans Patients Do Not Receive Statistically Different Quality Primary Care at Whitman-Walker Health, 2008–2016

Abstract: Purpose: Washington, DC, has the highest prevalence of transgender persons in the United States at 2.8%. Transgender persons in DC have lower income, less stable housing, and more HIV infection than nontrans persons. Data are scarce regarding primary care quality among trans persons. We provide a detailed analysis of transgender patients at Whitman-Walker Health, an HIV- and LGBT-focused community health center.Methods: We performed a retrospective electronic medical record review of transgender patients ≥18 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 14 publications
1
6
0
Order By: Relevance
“…Overall, our analysis suggests that TG/GD adolescents who are insured, accessing the healthcare system, and have at least one diagnosis code associated with gender dysphoria, receive similar, if not greater, levels of preventive health services compared to their cisgender peers. This aligns with previous studies using Medicare claims [19], Behavioral Risk Factor Surveillance System (BRFSS) data [33], and clinic-level data [34], which did not find a significant difference in primary care utilization between TG/GD and cisgender individuals.…”
Section: Discussionsupporting
confidence: 89%
“…Overall, our analysis suggests that TG/GD adolescents who are insured, accessing the healthcare system, and have at least one diagnosis code associated with gender dysphoria, receive similar, if not greater, levels of preventive health services compared to their cisgender peers. This aligns with previous studies using Medicare claims [19], Behavioral Risk Factor Surveillance System (BRFSS) data [33], and clinic-level data [34], which did not find a significant difference in primary care utilization between TG/GD and cisgender individuals.…”
Section: Discussionsupporting
confidence: 89%
“…The data represented cancer screening for four different anatomical parts. Eight studies described breast cancer [6–8,35,36,38,48,50], ten described cervical cancer [6–8,11,36,39,40,46,48,50], four described prostate cancer [7,9,10,50] and three described colorectal cancer [6,36,50]. Six articles reported results on multiple organs [6–8,36,48,50], therefore increasing the pool of data available for analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Meta-analysis for UTD versus LT was performed separately for each of the four cancer screening categories to maximise data capture – i.e., breast, cervix, prostate, colorectal. 11 of 18 studies were added to our meta-analysis [6–11,35,36,39,46,50]. Seven of 18 studies [38,40,41,43,45,48,49] could not be included in the quantitative synthesis due to missing data or lack of control groups prohibiting the calculation of OR.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, a study conducted among transgender men in the greater Boston area showed that 77.1% of participants had received Papanicolaou tests in the past 3 years. Finally, a retrospective single-center study found that transgender men were more likely to have had a lifetime Papanicolaou test than were cisgender women.…”
Section: Cancer Screeningmentioning
confidence: 99%